A Rare Septic Transfusion Reaction: Case Report - Caramia McQuaid; Christine M. Cahill; Debra Masel; Aimee Kievitt; Neil Blumberg; Majed A. Refaai (Research and Practice in Anesthesiology, 2017)
Transfusion of PRBCs is associated with an increased risk of adverse reactions. Complications may occur over a wide range of time from immediately during transfusion to days afterwards. These include allergic reactions, febrile non-hemolytic reactions, hemolysis, transfusion associated circulatory overload (TACO), transfusion-related acute lung injury (TRALI), transfusion-transmitted pathogens, and immune-mediated reactions.